1997
DOI: 10.1046/j.1365-3024.1997.d01-172.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response of Echinococcus granulosus infected mice: Protoscolex specific response during infection is associated with decreasing specific IgG1/IgG3 ratio as well as decreasing avidity

Abstract: The antibody response was followed during 68 weeks in 17 Balb/c mice intraperitoneally (i.p.) infected with Echinococcus granulosus protoscoleces (PSC) and in three mice i.p. immunized with dead PSC. Titres of antibodies recognizing peptidic and glucidic PSC epitopes, as well as their isotypic and avidity profiles were followed by ELISA. In addition, antigen recognition patterns were analysed by immunoblot. The response against carbohydrate epitopes was dominant in infected and immunized mice but stronger in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…The authors concluded that MF inhibited the production of a multitude of cytokines, regardless of the cell In conclusion, our results suggest that Em492 antigen may be an important molecule in the survival strategies employed by E. multilocularis metacestodes. Furthermore our results are in line with other studies that show that glycosylated moieties from different parasitic preparations of E. multilocularis and of E. granulosus induce significant humoral immune responses in experimental infection models (9,16,39,48). The present study serves as an initial step for further investigations on the biological relevance of the Em492 antigen during E. multilocularis infection.…”
Section: Vol 72 2004 Secretory Component Of E Multilocularis Metacsupporting
confidence: 91%
See 1 more Smart Citation
“…The authors concluded that MF inhibited the production of a multitude of cytokines, regardless of the cell In conclusion, our results suggest that Em492 antigen may be an important molecule in the survival strategies employed by E. multilocularis metacestodes. Furthermore our results are in line with other studies that show that glycosylated moieties from different parasitic preparations of E. multilocularis and of E. granulosus induce significant humoral immune responses in experimental infection models (9,16,39,48). The present study serves as an initial step for further investigations on the biological relevance of the Em492 antigen during E. multilocularis infection.…”
Section: Vol 72 2004 Secretory Component Of E Multilocularis Metacsupporting
confidence: 91%
“…A. Wilson, J. Jaeken, and R. A. Dwek, Letter, Glycobiology 11:10, 2001). Several biological activities of pathogen carbohydrates have been described, such as antigenic activity (23,39,48,50), inhibition of cellular proliferation (32,44,53,54), mimicry of host components (37,55), and other immunosuppressive and immunomodulatory effects (9,11,40,56). Dematteis et al (11) have isolated a carbohydrate-rich fraction named E4…”
mentioning
confidence: 99%
“…Furthermore, chronically infected mice maintained a markedly low-avidity IgG response to the LL antigen Em2(G11). A similar phenomenon had been observed in infections with the closely related parasite E. granulosus (43).…”
Section: Discussionsupporting
confidence: 76%
“…In this model, the host reacts to the protoscoleces producing innate local and adaptive systemic responses (Severi et al 1997).…”
Section: Discussionmentioning
confidence: 99%